(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Research competence is an essential component of effective teaching practice; nevertheless, many pre-service teachers have difficulties in developing the necessary knowledge, abilities, and confidence to engage in educational research. This study investigates the function of mentorship relationships in improving research proficiency among aspiring foreign language teachers at the Samarkand State Institute of Foreign Languages. This research used an interpretive phenomenological approach to investigate the lived experiences of 24 pre-service teachers and 12 faculty mentors engaged in structured mentoring over the course of one academic year. The data collection included extensive interviews, reflective journals, observations of mentoring sessions, and records from collaborative investigations. The findings suggest that mentorship improves research competence development through three primary mechanisms: transforming abstract research concepts into applicable pedagogical instruments, facilitating collaborative knowledge construction through dialogue, and fostering professional identity as research-informed practitioners. The study demonstrates that effective mentorship goes beyond the simple transfer of technical skills, facilitating significant transformations in how prospective educators see and engage with research as integral to their professional practice.